ARE LIQUIDITY, DIVIDEND POLICY, LEVERAGE, AND PROFITABILITY THE DETERMINANTS OF FIRM VALUE: EVIDENCE FROM THE LISTED FIRMS? - Chakraborty, Brishti; Maruf, Md. Yealid Hassan (Copernican Journal of Finance & Accounting, 2023)
The main rationale for conducting this study is to investigate the impact of liquidity, leverage, dividend, profitability, productivity, and working capital on the firm value of multinational companies. The data is collected from the listed firms in various categories under Dhaka Stock Exchange (DSE). Data are gathered from the financial statements of 38 concerned firms (having 228 observations) of various categories from the period 2015 to 2021. To examine the data, we have applied a two-stage least squares (2SLS) estimator. Findings and results reveal that the cash ratio, total asset turnover, and debt-asset ratio have a positive and significant relationship with firm value when calculated by the price-to-book value (PBV) ratio. Moreover, cash ratio, dividend payout ratio, and total asset turnover have positive as well as significant relationships with firm value when measured by market capitalization (MKC). This study may have a great contribution to analyzing the firm value by considering one new variable; market capitalization (MKC) for the first time. Such kind of study has very much important to analyze the financial condition and firm value of companies from emerging countries.